Automated Decision Technique for the Crowd Estimation Method Using Thermal Videos - Nermin K. Negied; Ayman El-Sayed; Asmaa S. Hassaan (Applied Computational Intelligence and Soft Computing)
Counting and detecting the pedestrians is an important and critical aspect for several applications such as estimation of crowd density, organization of events, individual’s flow control, and surveillance systems to prevent the difficulties and overcrowding in a huge gathering of pedestrians such as the Hajj occasion, which is the annual event for Muslims with the growing number of pilgrims every year. This paper is based on applying some enhancements to two different techniques for automatically estimating the crowd density. These two approaches are based on individual motion and the body’s thermal features. Theessential characteristic of crowd counting techniques is that they do not require a previously stored and trained data; instead they use a live video stream as input. Also, it does not require any intervention from individuals. So, this feature makes it easy to automatically estimate the crowd density. What makes this work special than other approaches in literature is the use of thermal videos, and not just relying on a way or combining several ways to get the crowd size but also analyzing the results to decide which approach is better considering different cases of scenes. This work aims at estimating the crowd density using two methods and decide which method is better and more accurate depending on the case of the scene; i.e., this work measures the crowd size from videos using the heat signature and motion analysis of the human body, plus using the results analysis of both approaches to decide which approach is better. The better approach can vary from video-to-video according to many factors such as the motion state of humans in this video, the occlusion amount, etc. Both approaches are discussed in this paper. The first one is based on capturing the thermal features of an individual and the second one is based on detecting the features of an individual motion. The result of these approaches has been discussed, and different experiments were conducted to prove and identify the most accurate approach. The experimental results prove the advancement of the approach proposed in this paper over the literature as indicated in the result section.